ALOX15B-based efferocytosis clusters: prognostic implications and immune cell infiltration in breast cancer - Juan Chen; Chang Zheng; Fei Zhang; Shiyao Sun; Guowen Liu; Guo Huang (Discover Oncology)
Abstract Objective Efferocytosis, a process of apoptotic cell clearance, is implicated in the initiation and progression of breast cancer. This study aims to construct an efferocytosis-related genetic risk model to evaluate its prognostic value and its association with immune infiltration in breast cancer. Methods The expression patterns of efferocytosis-related genes in breast cancer were analyzed, followed by clustering analysis to explore their relationship with tumor immune infiltration across different subtypes. A risk model based on efferocytosis-related genes was developed to predict breast cancer prognosis and assess its correlation with immune infiltration. Using this model, the association between ALOX15B expression and breast cancer survival was evaluated. In Vitro Functional Assays, the biological role of ALOX15B in breast cancer progression was investigated using the following approaches: Cellular Proliferation: MTT assay, EdU incorporation assay, and colony formation assay were performed to assess proliferation in MCF7 and MDA-MB-231 cells. Transwell was used to quantify migratory and invasive. Flow cytometry was conducted to evaluate cell cycle distribution. Western blotting was performed to assess Epithelial-Mesenchymal Transition marker expression. Results Clustering analysis of the expression of efferocytosis-related genes in breast cancer, Cluster A had a good prognosis and was closely associated with immune cell infiltration. Functional enrichment analysis of the activation and adaptation of immune response in Cluster A clustering may be an important factor in improving breast cancer prognosis. In addition, an immune-related gene risk model was constructed, which was found to be a valid predictor of breast cancer prognosis. Finally, it was highlighted that the expression of ALOX15B inhibited the proliferation, movement, invasion, and DNA replication capability of breast cancer cells. The growth of breast cancer cells was also impeded by ALOX15B, which hindered cell division during the G1 phase. The expression of ALOX15B is associated with the sensitivity of a variety of chemotherapeutic agents. Conclusion Efferocytosis-related models can be used for the assessment of breast cancer prognosis, while the efferocytosis-related gene ALOX15B can affect the migration and invasive ability of breast cells.